2015
DOI: 10.1021/nn507485j
|View full text |Cite|
|
Sign up to set email alerts
|

Hybrid Mesoporous Silica-Based Drug Carrier Nanostructures with Improved Degradability by Hydroxyapatite

Abstract: Potential bioaccumulation is one of the biggest limitations for silica nanodrug delivery systems in cancer therapy. In this study, a mesoporous silica nanoparticles/hydroxyapatite (MSNs/HAP) hybrid drug carrier, which enhanced the biodegradability of silica, was developed by a one-step method. The morphology and structure of the nanoparticles were characterized by TEM, DLS, FT-IR, XRD, N2 adsorption-desorption isotherms, and XPS, and the drug loading and release behaviors were tested. TEM and ICP-OES results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 49 publications
5
125
0
Order By: Relevance
“…Studies have shown that the degradation of mesoporous materials was faster than non-mesoporous materials, and the degradability of the ordered mesoporous materials was of great significance for their applications in biomedical materials. [31][32][33] Thus, this study further demonstrated that m-MS played a dominant role in the degradation of the composites because of the ordered pore structure, high specific surface area and high pore volume of m-MS. Fig. 5b exhibits the pH value changes of the solution after the samples were soaked in Tris-HCl for different times.…”
Section: Degradability Of M-ms/wp Compositessupporting
confidence: 58%
“…Studies have shown that the degradation of mesoporous materials was faster than non-mesoporous materials, and the degradability of the ordered mesoporous materials was of great significance for their applications in biomedical materials. [31][32][33] Thus, this study further demonstrated that m-MS played a dominant role in the degradation of the composites because of the ordered pore structure, high specific surface area and high pore volume of m-MS. Fig. 5b exhibits the pH value changes of the solution after the samples were soaked in Tris-HCl for different times.…”
Section: Degradability Of M-ms/wp Compositessupporting
confidence: 58%
“…This further confirmed that TP had been successfully embedded in the cavities of SCP nanospheres. Overall, the total loading capacity of TP in SCP was determined to be 45.6 wt.%, much larger than that in porous silica nanospheres [25] and mesoporous BG nanoparticles [13]. Fig.…”
Section: Resultsmentioning
confidence: 85%
“…16 In particular, biomaterials that exist abundantly in the body are good candidates for constructing biodegradable nanomaterials. Among various biomaterials, DNA has been used as a programmable building block for the assembly of different nanostructures.…”
Section: Introductionmentioning
confidence: 99%